Integration of renewable energy into San Andres Island electrical grid - Archbold, Keyla Newball; Zambrano, Alvaro; Rosero Garcia, Javier (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Renewable energy (RE) sources integration in electrical grids is changing the dynamics of planning and operation. Overvoltage, overcurrent, and malfunction of protection schemes are some effects if it is limits are not controlled. This article presents a methodology based on the hosting capacity (HC) concept to estimate performance indexes by considering stochastic methods and systematic simulation taking as study case the grid of San Andres Island. RE is of special interest in islands where diesel generators produce energy with a high footprint and security of supply is low as there is a high dependence on fossil fuels and their transport regime. The simulations are carried out in DigSilent PowerFactory integrated with Python to automate the iterations over different penetration levels. The most limiting factor found is transformer rating. Voltage rise is a factor to be monitored at the end of the circuits. Emissions are reduced with the introduction of renewable energies, but variability needs to be controlled as it could require fast start-up of generators; this modifies monitoring and control schemes to maintain stability. The limit found is higher than the established regulation for non-interconnected zones (NIZ) in Colombia, showing the capability of the grid to integrate RE.